2021
DOI: 10.3372/wi.51.51305
|View full text |Cite
|
Sign up to set email alerts
|

Maracujá on the rocks: a new Passiflora species (Passifloraceae sensu stricto) from the rupicolous ecosystems of the Brazilian Atlantic rainforest

Abstract: Here we describe a new species of Passiflora subg. Passiflora (Passifloraceae sensu stricto) found in the Brazilian Atlantic rainforest in areas of campos rupestres of the João Pinto formation in Minas Gerais and on granitic inselbergs of Espírito Santo. The new species, named Passiflora ita, is described, illustrated, compared to similar species and its conservation status is preliminarily assessed as Endangered (EN) following IUCN Red List categories and criteria, reinforcing the importance of the areas wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In the last few years there has been a significant increase in the number of studies in Scarabaeinae in Brazil, but in the Southeast region, more work is still needed on this subfamily. The Brazilian state of Espírito Santo, despite being located close to research centers, has few studies on the Scarabaeinae diversity (Louzada et al, 1996;Vaz-de-Mello, 2000;Schiffler et al, 2003;Vieira et al, 2008Vieira et al, , 2011 and the knowledge of the biodiversity in this region is urgent, given the large number of threatened species, number that has been increasing in recent years, with some species considered extinct locally (Fraga et al, 2019;Mezzonato-Pires et al, 2021). Knowing about (being aware of) this biodiversity gap, in this paper we sampled the dung beetle fauna in the Reserva Natural Vale (RNV) (Linhares, Espírito Biodiversidade Brasileira, 12(4): 1-15, 2022 DOI: 10.37002/biobrasil.v12i4.2186…”
Section: Study Areamentioning
confidence: 99%
“…In the last few years there has been a significant increase in the number of studies in Scarabaeinae in Brazil, but in the Southeast region, more work is still needed on this subfamily. The Brazilian state of Espírito Santo, despite being located close to research centers, has few studies on the Scarabaeinae diversity (Louzada et al, 1996;Vaz-de-Mello, 2000;Schiffler et al, 2003;Vieira et al, 2008Vieira et al, , 2011 and the knowledge of the biodiversity in this region is urgent, given the large number of threatened species, number that has been increasing in recent years, with some species considered extinct locally (Fraga et al, 2019;Mezzonato-Pires et al, 2021). Knowing about (being aware of) this biodiversity gap, in this paper we sampled the dung beetle fauna in the Reserva Natural Vale (RNV) (Linhares, Espírito Biodiversidade Brasileira, 12(4): 1-15, 2022 DOI: 10.37002/biobrasil.v12i4.2186…”
Section: Study Areamentioning
confidence: 99%
“…Recent work carried out along the eastern portion of Vale do Rio Doce, near the border with Espírito Santo, has highlighted the botanical diversity and biological shortfalls of the region through the description of new and endemic taxa from diverse lineages (Gonella et al, 2015;Mello-Silva, 2018;Kollmann, 2020;Andrino & Gonella, 2021;Antar et al, 2021aAntar et al, , 2021bMezzonato-Pires et al, 2021). This is especially true around the João Pinto Formation, a geological group of Neoproterozoic quartzites forming a small and fragmented mountain complex with campos rupestres vegetation (Oliveira, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, smaller disjunct patches of campos rupestres were discovered on quartzitic outcrops that are entirely inserted in the Atlantic Forest phytogeographic domain (Gonella et al 2015;Lopes et al 2016;Siniscalchi et al 2016;Mello-Silva 2018). These areas located in the Rio Doce valley in eastern Minas Gerais, namely Serra do Padre Ângelo, Pico da Aliança, and Sete Salões State Park, possess some floristic elements related to the ER (Siniscalchi et al 2016;Mello-Silva 2018;Andrino & Gonella 2021;Antar et al 2021a), but also to the granitic inselbergs typically found in the surrounding Atlantic Forest (Antar et al 2021b;Mezzonato-Pires et al 2021). With an increasing number of taxonomic novelties described in recent years, these areas corroborate the elevated species richness and endemism of the campos rupestres (Giulietti et al 1997;Fernandes 2016;Colli-Silva et al 2019), but also highlight the botanical sampling deficit in Brazil.…”
Section: Introductionmentioning
confidence: 99%